Proximate Analysis of Protein and Relative Growth of Tilapia Fish Exposed to Heat Stress and Fed with the Combination of Willow Leaf and Chromium - Ari Widodo; muhammad isa; teuku armansyah TR (Universitas Syiah Kuala, 2014)
This study was aimed to determine the effect of relative growth rate and proximate levels of protein in tilapia fish exposed to heat stress and supplemented with the combination of willow leaf powder and chromium. A total of 30 tilapia fish with 1.3-1.5 cm long were divided into 6 treatment groups with 5 repetitions: fed with commercial feed at temperature 29±1° C (P1S1), fed with commercial feed combined with willow leaf at temperature 29±1° C (P2S1), fed with commercial feed combined with willow leaf and chromium at temperature 29±1° C (P3S1), fed with commercial feed at temperature 35±1° C (P1S2), fed with commercial feed combined with willow leaf at temperature 35±1° C (P2S2), fed with commercial feed combined with willow leaf and chromium at temperature 35±1° C (P3S2). The treatments were carried out for 15 days. Then, relative growth rate and proximate levels of proteins were calculated using Kjedahl methods. The results showed that there was an increase of the mean of relative growth rate and proximate levels of protein. Based on statistical test using factorial completely randomized design it was showed that there was a significant effect (P0.01) on the interaction of feeding and temperature with the relative growth rate, but did not affect the relative growth rate of tilapia fish. The proximate level of tilapia fish protein was affected very significantly (P0.01) by the food and the interaction between food and temperature as well, while the temperature treatment gave no significant effect on the proximate level of tilapia fish protein. In conclusion, the commercial feed combined with willow leaf and chromium can increase the relative growth rate and the proximate level of protein of tilapia fish exposed to heat stress.Key words: relative growth rate, proximate protein, willow leaf, chromium, tilapia fish